1987
DOI: 10.1002/hrm.3930260403
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perception and Behavior in Mixed Gender Teams

Abstract: Leadership and conflict on male and female task teams of varying compositions are compared for groups constituted in the late 1960s/early 1970s and the mid‐1980s. The data indicates substantial increase in the leadership activities of women in mixed sex situations, striking decrease in conflict on predominantly female teams, and impressive improvement in the ability of young men to work with women on analytical tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Ely's work (1995) suggested that in occupations or industries in which women are well-represented, the association between successful leadership and masculinity may be less intense and more difficult to sustain. Recent work has also suggested significantly lower levels of work-related conflict in predominantly female work settings (Webber, 2006). Finally, Welbourne, Cycyota, and Ferrante (2007) found that women's leadership is associated with stronger short-and long-term performance, potentially increasing the visibility and recognition of women's leadership in industries with a strong female presence among top leaders.…”
Section: Not All Industries Are Created Equally: the Impact Of Sex Comentioning
confidence: 99%
“…Ely's work (1995) suggested that in occupations or industries in which women are well-represented, the association between successful leadership and masculinity may be less intense and more difficult to sustain. Recent work has also suggested significantly lower levels of work-related conflict in predominantly female work settings (Webber, 2006). Finally, Welbourne, Cycyota, and Ferrante (2007) found that women's leadership is associated with stronger short-and long-term performance, potentially increasing the visibility and recognition of women's leadership in industries with a strong female presence among top leaders.…”
Section: Not All Industries Are Created Equally: the Impact Of Sex Comentioning
confidence: 99%
“…Studies of emergent leadership in ongoing (i.e. semester-long) teams of business students typically find little evidence of sex differences, suggesting that the task behaviors of men and women do not differ when they interact over time (Goktepe & Schneier, 1989;Webber, 1987). Perhaps continued task interaction permits team members to provide information concerning their competence, which reduces the effect of sex on task behavior (Deaux & Major, 1987;Elsass & Graves, 1997;Harrison, et al, 1998).…”
Section: Effect Of Sexmentioning
confidence: 99%